Decreased growth of wild soil microbes after 15 years of transplant‐induced warming in a montane meadow - Alicia M. Purcell; Michaela Hayer; Benjamin J. Koch; Rebecca L. Mau; Steven J. Blazewicz; Paul Dijkstra; Michelle C. Mack; Jane C. Marks; Ember M. Morrissey; Jennifer Pett‐Ridge; Rachel L. Rubin; Egbert Schwartz; et al. (Global Change Biology, 2022)
The carbon stored in soil exceeds that of plant biomass and atmospheric carbon and its stability can impact global climate. Growth of decomposer microorganisms mediates both the accrual and loss of soil carbon. Growth is sensitive to temperature and given the vast biological diversity of soil microorganisms, the response of decomposer growth rates to warming may be strongly idiosyncratic, varying among taxa, making ecosystem predictions difficult. Here, we show that 15 years of warming by transplanting plant–soil mesocosms down in elevation, strongly reduced the growth rates of soil microorganisms, measured in the field using undisturbed soil. The magnitude of the response to warming varied among microbial taxa. However, the direction of the response—reduced growth—was universal and warming explained twofold more variation than did the sum of taxonomic identity and its interaction with warming. For this ecosystem, most of the growth responses to warming could be explained without taxon‐specific information, suggesting that in some cases microbial responses measured in aggregate may be adequate for climate modeling. Long‐term experimental warming also reduced soil carbon content, likely a consequence of a warming‐induced increase in decomposition, as warming‐induced changes in plant productivity were negligible. The loss of soil carbon and decreased microbial biomass with warming may explain the reduced growth of the microbial community, more than the direct effects of temperature on growth. These findings show that direct and indirect effects of long‐term warming can reduce growth rates of soil microbes, which may have important feedbacks to global warming.